MENGUKUR EFEKTIVITAS KEBIJAKAN PEMERINTAH: PENGENDALIAN DANA IDLE PEMERINTAH DAERAH - Maryadi Maryadi (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
Since the end of 2015 the government has established a policy for the conversion of Revenue Sharing Funds (DBH) and / or General Allocation Funds (DAU) in the form of non-cash as an effort to: a) Encourage the management of healthy, efficient and effective APBDs; b) Encouraging optimal and timely absorption of the local budget; and; c) Reducing cash and / or local government deposits in banks by an unnatural amount. This study is intended to determine the effectiveness of the implementation of the policy, especially in an effort to reduce cash and / or local government deposits in banks in an unnatural amount.